Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/1678-4499.007
|View full text |Cite
|
Sign up to set email alerts
|

Food quantity and quality of cassava affected by leguminous residues and inorganic nitrogen application in a soil of low natural fertility of the humid tropics

Abstract: ABSTRACT:The aim of this study was to test the hypothesis that the quality and quantity of biofortified cassava root in a humid tropical environment can be modified with the application of a combination of low-and high-quality residues of leguminous tree species. The experiment was designed as a 6 × 2 factorial (a combination of 4 legume species versus 2 levels of nitrogen) with 4 replications in a randomized block design and the following treatments: Gliricidia + Acacia, Gliricidia + Leucaena, Gliricidia + Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, the ionic composition of the soil solution influences organic matter state, particularly coagulation/dissolution (Oste et al 2002). The interactions between calcium, magnesium, and organic compounds derived of biomass decomposition can result in greater permanence of both calcium and magnesium in the soil, in turn improving the soil rootability and conditions for root growth (Moura-Silva et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ionic composition of the soil solution influences organic matter state, particularly coagulation/dissolution (Oste et al 2002). The interactions between calcium, magnesium, and organic compounds derived of biomass decomposition can result in greater permanence of both calcium and magnesium in the soil, in turn improving the soil rootability and conditions for root growth (Moura-Silva et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between calcium, magnesium, and organic compounds derived of biomass decomposition can result in greater permanence of both calcium and magnesium in the soil, in turn improving the soil rootability and conditions for root growth (Moura‐Silva et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…When studying Gliricidia and Leucaena alleys as a way to improve soil properties, Fernandes et al [27] found that the residues incorporated 160 and 130 kg ha −1 year −1 of N, respectively (when only considering N). The leguminous alleys recovered about 20% of N directly from the residues deposited in the soil [11][12][13][14][15][16]. BNF can also represent N inputs relevant to the soil/plant system and reduce the need for N fertilizer application, which is often expensive and most susceptible to losses [8].…”
Section: Macronutrient Leaf Contents and Productivitymentioning
confidence: 99%
“…Unsustainable agricultural practices for land use and management conducted by farmers in the humid tropics, such as along the periphery of the Amazon in the Brazilian state of Maranhão, are factors related [1] that increase soil degradation [2]. In addition, the practice of itinerant cutting and burning has accelerated deforestation in the Amazon [3,4].…”
Section: Introductionmentioning
confidence: 99%